Poetic discourse of Andrea Zlatar: a reading of the poetry collection "Uneven love" - Šunjić, Ivan (ZFD 10: Zbornik radova s Međunarodnoga znanstvenog skupa Zadarski filološki dani 10 održanog u Zadru 10. studenoga 2023., 2026)
The collection of poems Uneven Love (2002) is the only “pure” literary work of Andrea Zlatar. The collection has recently been republished in a digital edition. Already after its first publication, critics highly valued this poetic debut and marked its significance in the context of contemporary Croatian poetry. It was noted that this collection of poems fits into the “microclimate of new Croatian poetry” that was still undescribed by critics at the time, with sensitivity and intimacy that were missing in the previous “decade of hard core phenomenology” (Rade Jarak). However, the reading of the collection stopped at a few critical and reviewer texts. The work is the first detailed analysis and interpretation of this collection, which is characterized by a complex poetic exploration of the self, which is related to the author’s theoretical interests in autobiographical and diary discourse. In order to adequately unravel the complex “discourse world” of this poetic book, its intertextuality, intra-, inter- and metadiscursivity, we will use the methods of contemporary discourse stylistics and semiotics.